Social Media Influences for the English Students’ Speaking Ability at SMP Negeri 1 Kuala Batee - Herawati, Pipit; Efendi, Zuhri (Ridwan Institute, 2024)
Speaking is one of the most important skills when learning English. Speaking is also a way to convey ideas and thoughts clearly and intelligently through sentences addressed to the listener or interlocutor. The purpose of this study is to determine whether there is an effect on students' English speaking ability using social media at SMP Negeri 1 Kuala Batee. This research used quantitative approach with pre-experimental method with One-Group Pretest-Postest design. The sample of this research is the class of VIII students. MIA.1 which amounted to 23 students. Data collection was carried out using a test instrument. This study was analyzed using the data normality test to test the distribution of data and paired sample t-test to analyze the data. Based on the results of the Kolmogorov-Smirnov Test calculation is 0.200, this result is more than 0.05 which is the general significance level, which indicates that the Pretest data is considered normal, on the post test using the Kolmogorov-Smirnov test, the p-value obtained is 0.119, more than 0.05, this indicates that the post test data is considered normal. The increase in mean scores observed in the paired-samples t-test table shows the positive impact of using YouTube social media as a learning medium in improving students' English language skills. The results obtained in this study are the influences of social media for the English students’ speaking ability in class VIII.MIA.1 SMP Negeri 1 Kuala Batee.